Health Education On The Danger Signs Of Pregnancy In Primigravidan And Multigravida - Triguno, Yopita; Wardana, Ketut Eka Larasati; Ayu Wulandari, Ketut (Journal of Applied Nursing and Health, 2021)
Background: Maternal Mortality Rate (MMR) is one attempt to assess the degree of public health. One of the problems associated with maternal mortality is the problem of pregnancy that should be avoidable. Such pregnancy problems can be detected early from the presence of danger signs in pregnancy. One factor affecting mothers' knows the pregnancy hazard signs is maternal knowledge. Methods: Maternal Mortality Rate (MMR) is one attempt to assess the degree of public health. One of the problems associated with maternal mortality is the problem of pregnancy that should be avoidable. Such pregnancy problems can be detected early from the presence of danger signs in pregnancy. One factor affecting mothers' knows the pregnancy hazard signs is maternal knowledge. Results: The success of the implementation of this activity is obtained by analyzing pretest and posttest values. The average pretest and posttest results are 58,1018.55 respectively with the minimum, maximum (20, 60), and 79,329.26 values with minimum and maximum (90,100). The average difference in pretest and posttest values is 21.22 or reaches 36.5%. This increase in knowledge is statistically significant. Conclusion: The activity aims to educate pregnant women about the linking of pregnancy hazard signs. At the end of the activity, the purpose of the implementation of this activity was well achieved and targeted.